Impacts of forest management zones on termite attack frequency, intensity, and diversity in Wera Nature Tourism Park, Indonesia - ZULKAIDHAH ZULKAIDHAH; RUKMI RUKMI; DEWI WAHYUNI; ABDUL HAPID; HAMKA HAMKA (Society for Indonesian Biodiversity, 2026)
Abstract. Zulkaidhah, Rukmi, Wahyuni D, Hapid A, Hamka. 2026. Impacts of forest management zones on termite attack frequency, intensity, and diversity in Wera Nature Tourism Park, Indonesia. Biodiversitas 27 (4): d270407. https://doi.org/10.13057/biodiv/d270407. Forest management zoning may influence termite attack patterns and the composition of termite taxa associated with attacked vegetation. This study evaluated the effects of management zones and vegetation growth stages on termite attack frequency, attack intensity, and diversity patterns in Wera Nature Tourism Park (WNTP), Central Sulawesi, Indonesia. Field surveys were conducted using nested vegetation plots established across three management zones. Termite sampling was restricted to plants showing visible signs of attack within the vegetation plots, and specimens were identified primarily on the basis of morphological characteristics, especially soldier morphology. Attack frequency and intensity were analyzed using two-way ANOVA, whereas termite community structure was described using Shannon diversity, Margalef richness, Pielou evenness, and relative dominance indices. Both management zone and vegetation growth stage significantly affected termite attack frequency and attack intensity (p<0.001), with trees showing the highest vulnerability. The utilization zone had the highest attack intensity (27.07%), whereas the protection zone had the lowest (11.00%). A total of eight termite taxa representing five genera were recorded from attacked vegetation across the three management zones. Most taxa were identified to species level, whereas two taxa (Bulbitermes sp. and Odontotermes sp.) remained at genus level because available diagnostic characters were insufficient for reliable species-level identification. Diversity and richness of termite taxa associated with attacked vegetation were highest in the protection zone and lowest in the utilization zone. Nasutitermes matangensis was the most dominant and widely distributed taxon across zones. Because environmental drivers were not measured directly, the observed zonation effects should be interpreted as statistically supported associations rather than confirmed mechanisms. These findings highlight the value of zoning-based termite monitoring for adaptive forest conservation and sustainable ecotourism management in WNTP.